2003
DOI: 10.1111/j.1651-2227.2003.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between prenatal infant feeding intention and initiation and duration of breastfeeding: a cohort study

Abstract: Donath SM, Amir LH, ALSPAC Study Team. The relationship between prenatal infant feeding intention and initiation and duration of breastfeeding: a cohort study. Acta Paediatr 2003; 92: 352-356. Stockholm. ISSN 0803-5253 Aim: To report the relationship between maternal prenatal intention to breastfeed and the actual initiation and duration of breastfeeding. Methods: Pregnant women resident within Avon, UK, expected to give birth between 1 April 1991 and 31 December 1992 were recruited in a longitudinal cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
158
2
15

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(203 citation statements)
references
References 23 publications
28
158
2
15
Order By: Relevance
“…Though 39.9 % of the mothers were first-time mothers with no experience in breastfeeding, their early decision would pose a positive outcome in breastfeeding. A study by Donath & Amir had shown that the time intended to breastfeed was important in predicting breastfeeding initiation and duration (Donath & Amir, 2003). There was also found no difference in intended to breastfeed by BMI categories (p = 0.226), nevertheless, more than half of the mothers who had the intention to breastfeed were normal BMI (51.6 %).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Though 39.9 % of the mothers were first-time mothers with no experience in breastfeeding, their early decision would pose a positive outcome in breastfeeding. A study by Donath & Amir had shown that the time intended to breastfeed was important in predicting breastfeeding initiation and duration (Donath & Amir, 2003). There was also found no difference in intended to breastfeed by BMI categories (p = 0.226), nevertheless, more than half of the mothers who had the intention to breastfeed were normal BMI (51.6 %).…”
Section: Discussionmentioning
confidence: 86%
“…Mothers who had positive breastfeeding intention prenatally was linked to the longer duration of breastfeeding (Wang, Lau, Chow, and Chan, 2014) and prenatal intention appears to be significant predictors of breastfeeding initiation and duration (Donath and Amir, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le désir prénatal d'allaiter ou de ne pas allaiter prédit en grande partie le comportement de la mère après la naissance de l'enfant [20]. Ainsi, l'intention prénatale d'allaiter de manière prolongée est significativement associée à un allaitement prolongé [9,10,21].…”
Section: Facteurs De Choix Personnel (Intentions Motivations Décisiunclassified